Factores determinantes del acceso a créditos en los hogares de la parroquia San Buenaventura. - Castro Mazón, Evelyn Carolina (2018)
The access to financial credits is a very important issue it allows the socioeconomic progress of the people or communities, so the investigation is consigned to investigate and establish the factors when requesting a loan at homes of San Buenaventura parish. Basically, the problem is based on answering the following question: Which are the most significant factors for a person to access a credit or not? To answer it, the job has as a purpose to analyze the possible variables with greater significance to the assignment of credits, such as: age, gender, educational level, job, number of people for room, beneficiaries of state programs, own housing and natural risk. The type of methodology used has a quantitative, descriptive and correlational approach, allowing to compare the dependent variable that is the holding of credits with the independent variables which are: own housing, age, , gender, educational level, job, number of people for room, beneficiaries of state programs and natural risk. For the data collection of the research, the survey was used as an instrument, through the application of a questionnaire addressed to the heads of San Buenaventura parish households. In the sample, the number of families that exist in the sample was considered. The results obtained were analyzed by Probit and Logit models at STATA 12 statistical program. It can be seen that the most significant variables for access to credit within households are: employment, educational level and risk; mentioned in order of importance. The employment as well as the educational level take a direct relationship with the dependent variable, and the risk had an inverse relationship with the probability of credit access